Genetic variability of the Brazilian hair sheep breeds - Paiva, Samuel Rezende (2005)
ABSTRACT: The objectives of this work were to investigate the genetic structure of the Brazilian hair sheep breeds and to determine the origin of the Santa Inês breed. Molecular similarity was determined using Randomly Amplified Polymorphic DNA - Polymerase Chain Reaction markers in 238 individuals from five naturalized sheep breeds: Santa Inês (48 animals), Rabo Largo (48), Somali (48), Morada Nova (48) and Bergamasca (46), collected in Goiás, Sergipe, Bahia, and Ceará States as well as in the Federal District. Fifty-four loci were selected from 19 primers, after a pilot test using 140 primers. Qualitative analyses indicate diagnostic markers for all breeds. All breeds were significantly different from each other. Interbreed differences were explained by 14.92% of the total variation. Santa Inês clustered with Bergamasca (97% bootstrap) and with Rabo Largo, composing the third member of the group (81% bootstrap) while Morada Nova and Somali breeds clustered separately. Each breed should be considered as a separate management and conservation unit, and special care should be taken with Rabo Largo, Morada Nova and Somali breeds, represented by small herds in Brazil. ___________________________________________________________________________________ RESUMO